A rotation method to calibrate BPM electric offsets. (November 2019) - Wang, M.W.; Wang, D.; Wang, Z.M.; Qiu, M.T.; Zheng, S.X.; Ma, P.F.; Guan, X.L.; Huang, W.H.; Wang, X.W.
Abstract: Beam position monitor is a key instrument for machine commissioning. To measure beam position accurately, offline calibrations to acquire the sensitivity and offsets of the BPM are essential prerequisites. A new method to calibrate the BPM electric offset is proposed in this paper. By measuring the location variation of the BPM electric center after rotating the BPM 180 degrees, the BPM offset can be derived. The method is more convenient, universal and accurate than the traditional methods. The method is successfully applied to calibrate the button BPM of Xi'an Proton Application Facility. The repetitive measurement error is 20.8 μm.